2016
DOI: 10.1007/s13277-016-5096-9
|View full text |Cite
|
Sign up to set email alerts
|

S100A16 promotes cell proliferation and metastasis via AKT and ERK cell signaling pathways in human prostate cancer

Abstract: S100A16 is a member of the S100 calcium-binding protein family. It is overexpressed in many types of tumors and associated with proliferation, migration, and invasion; however, its function in human prostate cancer is unresolved. Our objective was to determine its effects and the underlying pathways of S100A16 in prostate cancer tissues and cells. We measured S100A16 expression by quantitative real-time polymerase and Western blotting in eight matched prostate cancer and adjacent normal tissues, and in three p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
49
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 51 publications
(51 citation statements)
references
References 21 publications
2
49
0
Order By: Relevance
“…We observed that inhibition of ERK activation by U0126 increased the expression of p21 and p27 mRNA levels, suggesting that a decrease in p-ERK seems to be involved in the alteration of p21 and p27 mRNA expression during hair cell regeneration. These results are consistent with previous data showing that ERK activity contributes to the down-regulation of p21 and p27 that precedes cell cycle progression (Kortylewski et al, 2001; Villanueva et al, 2007; Hwang et al, 2009; Zhu et al, 2016; Seo et al, 2017). The possibility that other signaling pathways are involved in controlling p21 and p27 during hair cell regeneration cannot be excluded from our results.…”
Section: Discussionsupporting
confidence: 93%
“…We observed that inhibition of ERK activation by U0126 increased the expression of p21 and p27 mRNA levels, suggesting that a decrease in p-ERK seems to be involved in the alteration of p21 and p27 mRNA expression during hair cell regeneration. These results are consistent with previous data showing that ERK activity contributes to the down-regulation of p21 and p27 that precedes cell cycle progression (Kortylewski et al, 2001; Villanueva et al, 2007; Hwang et al, 2009; Zhu et al, 2016; Seo et al, 2017). The possibility that other signaling pathways are involved in controlling p21 and p27 during hair cell regeneration cannot be excluded from our results.…”
Section: Discussionsupporting
confidence: 93%
“…This member of the S100 protein family has been reported to be involved and overexpressed in several pathological affections, including cancer, but with different and often contradictory roles [119][120][121]. In our tumor tissues we found a single form of S10AG with a 3x fold increase versus the normal tissues.…”
Section: S10ag (S100a16)mentioning
confidence: 49%
“…In addition, ERK is associated with the proliferation of cancer cells and tumor invasion via degradation of extracellular matrix proteins. 42 Review studies documented the ERK can activate transcription factors, such as c-myc and NF-kB. 43 This makes ERK1/2 an important anti-prostate cancer target.…”
Section: Discussionmentioning
confidence: 99%